Employee perception of whistleblowing in the workplace: A systematic bibliometric review - Mohamad Reeduan, Mustapha; Muhammad Ashraf, Fauzi; Ong, Tian Soon; Leow, Hon Wei; Cheok, Mui Yee (The Elite Scientific Forum, 2024)
This paper systematically reviews employee perceptions of whistleblowing in the workplace. The theoretical foundation of this paper lies in the study of whistleblowing as an integral part of internal control systems for fraud prevention in organizations. About 806 publications in the Web of Science database were analyzed using a bibliometric approach entailing bibliographic coupling and co-word analysis. The review explores the study of whistleblowing, which is constantly rising as a result of the fact that many countries are strengthening their organizational whistleblowing systems. It is anticipated that more publications will be generated in the future years. The empirical results of this study indicate that a positive corporate working environment should be promoted from the top down and cultivated horizontally. The findings of this study, which were based on actual evidence, are helpful from a pragmatic point of view. Specifically, companies would need to foster a corporate climate that makes it easier for employees to report any probable or seen misconduct to higher authorities. This paper presents a novel knowledge structure by mapping employee perceptions regarding whistleblowing in the context of minimizing ongoing wrongdoings in organizations based on bibliometric analysis. Moreover, future studies should address organizational culture or the role of leadership in employee whistleblowing.